Correlation between parents role and women’s marital age in the religious affairs office - Yekti Satriyandari; Yunita Mayasari (Universitas 'Aisyiyah Yogyakarta, 2020)
The purpose of the study was to find out the correlation between the parents role and women's marital age in the Religious Affairs Office of Kasihan district. The study used a cross sectional approach and the type of descriptive correlational study. The subjects of the study were 48 brides who were going to get married at the Religious Affairs Office of Kasihan district which were retrieved using quota sampling method. The study used bivariate chi square analysis. The results of the study revealed that most respondents got married at mature ages namely 21 - 34 years old. There is a correlation between parents role and women’s marital age in the Religious Affairs Office of Kasihan district with a significance value of 0,000 (p 0,05) and the value of the correlation coefficient was 0,558. The Religious Affairs Office of Kasihan district should continue to cooperate with Kasihan Health Center to develop the implementation of the bridal class program and reproductive health education for prospective brides.